Electronic states and exciton dynamics in dicyanovinyl-sexithiophene on Au(111) - Bogner, Lea; Yang, Zechao; Baum, Sebastian; Corso, Martina; Fitzner, Roland; Bäuerle, Peter; Franke, Katharina J.; Pascual, José Ignacio; Tegeder, Petra (The journal of physical chemistry. C, Energy, materials, and catalysis, 2016)
Dicyanovinyl (DCV)-substituted oligothiophenes are often used as donor materials in vacuum-processed small-molecule organic solar cells, which exhibit promising efficiencies up to 10%. We combine scanning tunneling microscopy/spectroscopy and two-photon photoemission (2PPE) to obtain a complete picture of the electronic structure of DCV-sexithiophene (DCV6T) adsorbed on a Au(111) surface. We thus show that the transport gap amounts to 1.4 eV. We also identified an excitonic state possessing a binding energy of 0.6 eV. Using femtosecond time-resolved 2PPE, we followed the dynamics of optically excited electronic states at different molecular layer thicknesses. In the multilayer regime, we resolved the decay dynamics of excitonic states involving processes ranging from femtoseconds to several tens of picosseconds. The decay of the excitonic states is considerably slower than in DCV-dimethyl-pentathiophene (DCV5T-Me2). We ascribe this behavior to weaker intermolecular couplings in the DCV6T film. Despite the faster exciton decay, DCV5T-Me2 is known for a better solar cell efficiency compared to that of DCV6T. We suggest that this is due to the concomitant better exciton and charge carrier transport in well-coupled DCV5T-Me2 molecular structures.
Gesehen am 14.05.2020